Adaptive and Reference Shaping Control for Steer-By-Wire Vehicles in High-Speed Maneuvers. Issue 20 (2021) - Srinivasan, Srivatsan; Schmid, Matthias J.; Krovi, Venkat
Abstract: The growing adoption of steer-by-wire (SbW) systems in (semi-)autonomous vehicles provide a unique opportunity to exploit steering control for vehicle stability systems. In our previous work, we introduced a feedforward controller for an SbW vehicle employing optimal reference shaping and demonstrated reduced yaw disturbances during fast (evasive) maneuvers. Despite its beneficial effect on damping undesirable oscillations, open-loop input shaping can lead to unreliable trajectory tracking without additional feedback compensation in the presence of parameter inaccuracies and model uncertainties. In this study, we significantly advance the previous idea by combining a model reference adaptive control (MRAC) framework with an input shaper. Here, the MRAC framework converges quickly and maintains a nominal 'inner loop' behavior for the input shaper during high-speed maneuvers. This work includes stability and boundedness proof as well as extensive simulations.